Antibody responses to chimeric peptides derived from parasite antigens in mice and other animal species. (February 2019) - Orbegozo-Medina, R.A.; Martínez-Sernández, V.; Folgueira, I.; Mezo, M.; González-Warleta, M.; Perteguer, M.J.; Romarís, F.; Leiro, J.M.; Ubeira, F.M.
Abstract: Peptide vaccines constitute an interesting alternative to classical vaccines due to the possibility of selecting specific epitopes, easy of production and safety. However, an inadequate design may render these peptides poorly immunogenic or lead to undesirable outcomes (e.g., formation of B neoepitopes). As an approach to vaccine development, we evaluated the antibody response to chimeras composed of two or three known B epitopes from Trichinella and Fasciola, and several linkers (GSGSG, GPGPG and KK) in species as different as mice, sheep and turbot. All these species could mount an effective immune response to the short chimeric peptides. Nevertheless, this response depended on several factors including a favorable orientation of B-cell epitopes, adequateness of linkers and/or probability of formation of T neoepitopes. We also observed that, at least in mice, the inclusion of a decoy epitope may have favorable consequences on the antibody response to other epitopes in the chimera.